Perceived Usefulness and Learning Motivation: Evaluating Low-Barrier Augmented Reality in Foreign Language Acquisition - Destina Kasriyati; Refika Andriani; Syahdan Syahdan (FKIP Universitas Lampung, 2026)
This study aims to analyze students' perceptions and motivations in acquiring English language skills through the integration of “low-barrier” Augmented Reality (AR) technologies, such as Google Lens and QR codes. The urgency of this research lies in providing empirical data on the effectiveness of accessible technology as a learning bridge for students in developing countries facing educational paradigm shifts in the digital age. A quantitative approach with a survey design was employed, involving 58 fourth-semester students from the English Education Study Program at Universitas Lancang Kuning. Data were collected using a closed-ended questionnaire adapted from the ARCS (Attention, Relevance, Confidence, Satisfaction) model, which had undergone rigorous validity and reliability testing. The findings revealed that students' perceptions fell within the moderate category, with an average score of 2.98. Pearson Product-Moment correlation analysis showed a very strong and significant positive linear relationship (r = 0.886; p < 0.001) between students' perceptions and their learning motivation. The coefficient of determination (R^2 = 0.784) indicated that approximately 78.4% of the variance in learning motivation can be explained by the student perception variable. The